ANALISIS FINANSIAL USAHATANI TANAMAN TARUM (Indigofera tinctoria) : FINANCIAL ANALYSIS OF TARUM (Indigofera Tinctoria) - linda mahdalina linda (Universitas Widya Gama Mahakam, 2024)
The Indigo plants have the potential as fodder for Pasundan cattle and can also be cultivated on dry land, as a land use and maintain soil erosion and stability to improve soil quality. This research was conducted in Bantarkalong District on land owned by Mr. Ijaj. This method uses a case study using primary data, namely interviews with respondents to get related data to support research. The amount of Tarum farming costs is IDR. 13,596,000/ha/season, with details consisting of fixed costs of IDR. 2,523,500/ha/season and the amount of variable costs is IDR. 11,072,500/ha/ planting season. While the amount of revenue is IDR. 44.000,000, so that when juxtaposed with the amount of costs, tarum crop farming earns an income of IDR. 30,076,000/ha/season. And obtained an R / C value of 3.2 The R / C value of the tarum plant cultivation business is more than one, so the tarum plant cultivation business carried out by the respondent farmers can be said to be feasible to be cultivated. This means that every IDR. 1 cost incurred by the respondent will generate revenue of IDR. 3,2 and get a profit of IDR. 2.2 This value is quite large and shows that this farm is feasible to run. Kata kunci : Farm viability, case study, tarum plant